Association of mesenteric lymphadenitis with abdominal pain in children – A case–control study - Binchu Kurian,; Prince Philip,; Peter Prasanth Kumar Kommu, (Asian Journal of Medical Sciences, 2024)
Background: Enlarged mesenteric lymph nodes (MLNs) are a frequent ultrasonography finding in children with abdominal pain. Studies have shown that the incidence of enlarged mesenteric lymph nodes varies widely from 14% to 86%. The site, size, and number of lymph nodes are the distinguishing criteria for abnormal lymphadenopathy from normal lymph nodes. Aims and Objectives: The aims and objectives of the study are to estimate the prevalence of mesenteric lymphadenitis in children aged 4–15 years, who have abdominal pain with age and sex-matched controls without abdominal pain. Materials and Methods: The study was conducted after getting approval from the Institutional Ethics Committee. The MLN of all sizes was evaluated and measured using an ultrasound abdomen. Age and gender-matched controls were included in the study. Children with MLN were divided into 2 groups based on the size of the lymph nodes. (group A-MLN <4 mm and group B MLN >4 mm). In some cases, the site and size of MLN were noted and correlated with the severity of abdominal pain. Results: The ultrasonogram of the abdomen revealed that 15 (22.7%) cases had ≤4 mm nodes and 38 (57.6%) had >4 mm nodes. Out of the 38 cases, 2 (3.8%) had >10 mm nodes. Among the controls, 16 (24.2%) had ≤4 mm, 8 (12.1%) had >4 mm nodes, and none had MLN >10 mm. The odds ratio (OR) of cases having mesenteric lymphadenitis over controls was 5.067 (OR=5.067). Conclusion: Based on the results of our study, mesenteric lymphadenopathy >4 mm is associated with abdominal pain in children aged 4–15 years.